Is abdominal pain after an injury just an injury? Case report of rare aspiration pneumonia with lung gangrene and peritoneal response in a 5-year-old child - Hrubovčák, Ján; Tulinský, Ubomír; Ihnát, Peter; Jelínek, Petr; Slívová, Ivana; Mitták, Marcel; Roman, Jan; Stránský, Jan (Casopis lekaru ceskych, 2023)
Although pneumonia presents a relatively common diagnosis, it does not always present with classic clinical symptoms, nor does it follow a regular course without complications. The presented case describes a rare case of aspiration necrotizing pneumonia, which despite intensive therapy, progressed to lung gangrene and required a lung lobectomy. Another peculiarity is that the correct diagnosis was established only after the onset of abdominal pain, surprisingly by a trauma surgeon. This case emphasizes the necessity of a thorough general examination and draws attention to a rare, but conservatively intractable necrotizing pneumonia complicated by lung gangrene.
Keywords: necrotizing pneumonia; gangréna; bolesti břicha; Lobectomy; Pneumonia, Aspiration; Pneumonia, Necrotizing; acute abdomen; Abdominal pain; paediatrics; aspirační pneumonie; Pediatrics; Child, Preschool; Gangrene; Abdominal Pain; abdominal pain; plíce; předškolní dítě; Humans; nekrotizující pneumonie; Lung; lidé